Speak no evil - Iweala, Uzodinma (New York : HarperCollins Publishers, 2018)
An athlete from a private school in Washington, D.C., and his friend, the daughter of government insiders, struggle with the responses to the young man's sexual orientation before finding themselves speeding toward a violent future.
Keywords: Sexual orientation -- Fiction; Gay teenagers -- Fiction; Nigerian Americans -- Fiction; Sex -- Psychological aspects -- Fiction; Gay teenagers -- Fiction; Nigerian Americans -- Fiction; Washington (D.C.) -- Fiction; Washington (D.C.) -- Fiction